2020
DOI: 10.1038/s41598-020-76205-z
|View full text |Cite
|
Sign up to set email alerts
|

Naturally-occurring myopia and loss of cone function in a sheep model of achromatopsia

Abstract: Achromatopsia is an inherited retinal disease characterized by loss of cone photoreceptor function. Day blind CNGA3 mutant Improved Awassi sheep provide a large animal model for achromatopsia. This study measured refractive error and axial length parameters of the eye in this model and evaluated chromatic pupillary light reflex (cPLR) testing as a potential screening test for loss of cone function. Twenty-one CNGA3 mutant, Improved Awassi, 12 control Afec-Assaf and 12 control breed-matched wild-type (WT) Awass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Cases of cone dystrophy, cone-rod dystrophy and color vision defect caused by OPN1LW/OPN1MW mutation could had different levels of myopia manifestation [23]. Ross et al demonstrated that loss of cone function causes naturally-occurring myopia in sheep [24] and on this basis we hypothesize that ARR3 cause myopia through functional changes in cones.…”
Section: Discussionmentioning
confidence: 71%
“…Cases of cone dystrophy, cone-rod dystrophy and color vision defect caused by OPN1LW/OPN1MW mutation could had different levels of myopia manifestation [23]. Ross et al demonstrated that loss of cone function causes naturally-occurring myopia in sheep [24] and on this basis we hypothesize that ARR3 cause myopia through functional changes in cones.…”
Section: Discussionmentioning
confidence: 71%
“…In domestic animals, to this point in sheep [11][12][13] and dogs [19][20][21][22] (previously reported as cone degeneration and canine hemeralopia), the underlying genetics of different forms of achromatopsia are reported. Cones alone are affected in Alaskan Malamute (OMIA 001365-9615) and the German shorthaired pointers (OMIA 001676-9615) because of breed specific mutations in CNGB3, a cone-specific gene.…”
Section: Discussionmentioning
confidence: 93%
“…In sheep, a form of CNGA3-related achromatopsia has been characterized (OMIA 001481-9940) [11]. This ovine condition was intensively used for functional restoration of cone function [12], highlighting the biomedical value of such large animal models [13,14] in addition to the direct benefits for animal breeding and animal health.…”
Section: Introductionmentioning
confidence: 99%
“…Achromatopsia is an inherited retinal disease characterized by early loss of cone photoreceptors and later rod photoreceptor loss 31 , 138 , 139 . In a zebrafish model of human achromatopsia ( pde6c w59 ), cone photoreceptors expressed high levels of RIPK1/3, whereas rod photoreceptors were immunopositive for caspase-3, indicating activation of apoptosis 31 .…”
Section: Necroptosis Drives Death Of Retinal Cells In Retinal Disease...mentioning
confidence: 99%